Microstructure and Properties of Polyhydroxybutyrate-Chitosan-Nanohydroxyapatite Composite Scaffolds - L. Medvecky (The Scientific World Journal)
Polyhydroxybutyrate-chitosan-hydroxyapatite (PHB-CHT-HAP) composite scaffolds were prepared by the precipitation of biopolymer-nanohydroxyapatite suspensions and following lyophilisation. The propylene carbonate and acetic acid were used as the polyhydroxybutyrate and chitosan solvents, respectively. The high porous microstructure was observed in composites and the macroporosity of scaffolds (pore sizes up to 100 μm) rose with the chitosan content. It was found the reduction in both the PHB melting (70°C) and thermal degradation temperatures of polyhydroxybutyrate and chitosan biopolymers in composites, which confirms the mutual ineraction between polymers and the decrease of PHB lamellar thickness. No preferential preconcentration of individual biopolymers was verified in composites, and the compressive strengths of macroporous PHB-CHT-HAP scaffolds were approximately 2.5 MPa. The high toxic fluorinated cosolvents were avoided from the preparation process.